The Role of Social Media Instagram @Eye.On.Palestine in Increasing Social Awareness and Humanitarian Action - Faaizati, Kamila Khusnul; Aprilia, Rizki (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
In the growing digital era, social media has become an integral part of the daily life of the global community. One of the most popular social media platforms today is Instagram. This research aims to find out how the role of social media instagram @Eye.On.Palestine in increasing social awareness and humanitarian action. This research uses the Elaboration Likelihood Model theory with data collection techniques in the form of interview techniques and content analysis. Data analysis techniques are carried out simultaneously with the data collection process and to test the validity of the data, source triangulation is carried out to obtain accurate and accountable data. The results of this research can be a reference for humanitarian organisations and social activists in optimising the use of social media for similar purposes.